2019
DOI: 10.1371/journal.pone.0219116
|View full text |Cite
|
Sign up to set email alerts
|

Epidural morphine improves postoperative analgesia in patients after total knee arthroplasty: A randomized controlled trial

Abstract: Background Patients after total knee arthroplasty (TKA) often develop moderate to severe pain. This study compared the analgesic effect of low-dose epidural morphine vs. a comparable saline injection in patients following TKA surgery. Methods This randomized, double-blinded, and placebo-controlled trial was conducted in a tertiary hospital in Beijing between July 1, 2017 and May 30, 2018. One hundred and ten patients following TKA under combined spinal-epidural anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…All previous studies and case reports demonstrated the superiority of QL block for post-operative analgesia and lower opioid usage with all its side effects, on contrary; Irwin R. et al [29] in there 2020 published study concluded that parturient receiving bilateral QL block after caesarean section did not show any reduction in 24 hour morphine consumption by PCA versus those who received sham block. Although epidural morphine shows marvellous results for post-operative analgesia in plenty of published studies and an effect lasting 24 to 48 hours in some literature like Duale C et al [30] and Meng ZT et al [31], this was not the condition in our study in which the analgesic effect lasted only for 6 hours postoperatively. This can be explained by the nature of the surgery which includes three incisions; one midline and two groin incisions, also the ischaemic component of pain which is frequently encountered in patients with peripheral vascular disease.…”
Section: Discussioncontrasting
confidence: 67%
“…All previous studies and case reports demonstrated the superiority of QL block for post-operative analgesia and lower opioid usage with all its side effects, on contrary; Irwin R. et al [29] in there 2020 published study concluded that parturient receiving bilateral QL block after caesarean section did not show any reduction in 24 hour morphine consumption by PCA versus those who received sham block. Although epidural morphine shows marvellous results for post-operative analgesia in plenty of published studies and an effect lasting 24 to 48 hours in some literature like Duale C et al [30] and Meng ZT et al [31], this was not the condition in our study in which the analgesic effect lasted only for 6 hours postoperatively. This can be explained by the nature of the surgery which includes three incisions; one midline and two groin incisions, also the ischaemic component of pain which is frequently encountered in patients with peripheral vascular disease.…”
Section: Discussioncontrasting
confidence: 67%
“…Single epidural morphine administration is common and widely used for postoperative analgesia. [14][15][16][17] Epidural administration of sufentanil-morphine combinations improves the mother's ability to mobilize and interact with her newborn infant. 18 Epidural administration of morphine at a single dose of 3 mg /24 hours causes no respiratory depression and potential for catheter-related complications in patients undergoing cesarean sections.…”
Section: Discussionmentioning
confidence: 99%
“…111,112 One randomized controlled trial found that of 110 patients undergoing TKA, those who received epidural morphine had less severe pain scores and consumed significantly less opioids at the 48-hour mark compared with patients who received placebo (p < 0.002). 113 Intrathecal analgesia is an alternative to epidural analgesia in which medications are injected directly into the cerebrospinal fluid (CSF). 114 Intrathecal morphine (ITM) is commonly used, and when compared to control patients receiving bupivacaine spinal anesthesia alone, ITM administration has been found to improve pain scores at postoperative day zero and reduce initial postoperative opioid consumption following TKA.…”
Section: Prescription Medications and Multimodal Pain Regimensmentioning
confidence: 99%